Effects of gonadotropin-inhibitory hormone on early and late stages of spermatogenesis in ex-vivo culture of zebrafish testis - Fallah, Hamideh P.; Rodrigues, Maira S. [UNESP]; Zanardini, Maya; Nobrega, Rafael H. [UNESP]; Habibi, Hamid R. (Elsevier B.V., 2021)
Gonadotropin-inhibitory hormone (Gnih) is known to play a role in the regulation of reproduction in vertebrates by influencing gonadotmpin release and synthesis. While the endocrine actions of Gnih have been identified in several species, its paracrine/autocrine effects in the control of spermatogenesis are less defined. We have used ex vivo culture of zebrafish testis to investigate the role of gonadal zebrafish Gnih (zGnih) in the regulation of the spermatogenic process. We used FACScan cell cycle analysis, morphometric quantifications, BrdU incorporation and caspase-3 activity assays as well as measuring 11-Ketotestosterone (11-KT) level in the culture media. FACScan analysis and morphometric quantification results demonstrated direct action of zGnih on basal and gonadotropin (Lh and Fsh)-induced spermatogenesis. Treatment with zGnih (10 nM) significantly decreased the number of G0/G1 cells after 7-days of culture while no significant changes were found in the proportion area of spermatogonia cell types. Investigation of DNA synthesis using BrdU (5-Bromo-2'-Deoxyuridine) labeling showed that treatment with zGnih (10 nM) significantly decreased proliferative activity of type A spermatogonia, while increased the mitotic activity of type B spermatogonia. We also showed that treatment with zGnih (100 nM) completely eliminated 11-KT release induced by 100 ng/ml Fsh. Treatment with zGnih (10 and 100 nM) also inhibited both hCG and Fsh-induced spermatogenesis. These results, plus our previous findings, demonstrate that zGnih produced locally in the testis is a component of a complex multifactorial system that regulates testicular function in zebrafish.
Keywords: Gonadotropin-inhibitory hormone (Gnih); Human chorionic gonadotropin (hCG); Follicle-stimulating hormone (Fsh)